Integrating lean thinking and mathematical optimization: A case study in appointment scheduling of hematological treatments - Alessandro Agnetis; Caterina Bianciardi; Nicola Iasparra (Operations Research Perspectives, 2019)
This paper addresses the relationship between lean thinking and mathematical optimization. We discuss the roles of the two approaches, using as a reference case study the appointment scheduling process in a hematological center of a large Italian hospital. We report on how lean tools have been deployed to improve the process, we present a mathematical optimization model and discuss its implementation. Our aim is to show that the joint use of lean thinking and mathematical optimization can disclose large benefits when they are properly integrated in the improvement process. In our case study, simulated experiments point out that the average patient lead time could be decreased by more than 30%.
Keywords: 330; Appointment scheduling; Hematological treatments; Lean thinking